Cylindrical shells and panels subject to bilateral and unilateral contact constraints - McGlennon da Rocha Régis; Ricardo Azoubel da Mota Silveira; Christianne de Lyra Nogueira; Paulo B. Gonçalves (REM: International Engineering Journal)
Abstract The cylindrical shell-medium (soil or rock) contact problem solution is typically achieved through numerical methods, where the modeling or approximation of the medium’s behavior is usually made considering it as an elastic deformable foundation that does not react to tensile forces (unilateral contact problem). The purpose of this study is to develop a computational tool, using the Fortran programming language, aimed at a nonlinear problem involving cylindrical shells or panels under contact constraints imposed by a deformable soil. The analyses considered encompass unilateral and bilateral contact constraints imposed by the medium. The chosen method for discretizing the partial differential equilibrium equation contact problem is the finite difference method (FDM). This study considers the structure-medium contact problem in situations where the medium is approximated by the Winkler type model (one-parameter) or Pasternak type model (two-parameters), and the bilateral and unilateral contact situations are assessed. The research compares the efficiency of solution methods and highlight the strengths and weaknesses of each numerical approach proposed. The focus on FDM is particularly relevant for simulating the elastic base models commonly used in research.